TQM and Knowledge Management Impacts on SME Performance (Global Business Management Review (GBMR), 2022)
The purpose of this study is to examine the impact of Total quality management, Knowledge management and business performance of small and medium enterprises in Nigeria. SMEs are important to the economic growth of Nigeria, they are the major source of employment, innovation, poverty alleviation as well as the improvement of living standards. The study employed cross sectional research design, using structured questionnaire survey with a sample of 640 SMEs fully operational in Kano state, a total of 511 valid questionnaires were completed and returned representing 79.8 percent response rate. The finding from the study shows that the relationship between TQM, KM and business performance was found to be significant. The finding of this study will benefit owner/managers of SMEs, regulatory agencies, government at all levels and will also serve as a frame to future studies. Research limitations and direction for future studies discussed.